Pengelolaan Invoice dalam Subdivisi Accounts Payables pada PT Vidio Dot Com - Maria Rosari; Nila Pusvikasari; Agustinus Sri Wahyudi; Stella Stella (Jurnal Abdimas Sosial, Ekonomi, dan Teknologi, 2023)
The MBKM Program aims to provide opportunities for Indonesian students to gain work experience from quality partners, and improve their competencies so they can compete in the world of work. This final report describes the writer’s experience while participating in an internship at PT Vidio Dot Com as accounts payable intern a subdivision on accounting division. In this MBKM activity the writer is assigned to assist operational activities in the finance and accounting division which will be explained more fully in this report, such as manage invoices, recording of asset number, data recapitulation, reconciliation of E-Commerce SVOD Revenue data, and making Accounts Payable Performance Report. Through this MBKM activity, the writer have the opportunity to improve their skills, for soft skills such as the ability to communicate across functions and organizational levels and presentation skills, for technical skills such as using Microsoft Excel in analyzing data, Google Workspaces (google slides, google sheets, and email), and Smartsheet.